Exploring continuum structures in reactions with three-body nuclei. (December 2020) - Casal, J.; Gómez-Ramos, M.; Moro, A. M.; Corsi, A.
Abstract: The Transfer to the Continuum method has been applied to describe the 11 Li( p, pn ) and 14 Be( p, pn ) reactions in inverse kinematics, using structure overlaps computed within a full three-body model for the projectile. Calculations agree with the available experimental data on the unbound 10 Li and 13 Be nuclei.